Management of sickle cell disease: what to do when there is no evidence base - Lanzkron, Sophie (Henry Stewart Talks, 2019)
The pathophysiology of vaso-occlusive crises (VOC) in sickle cell disease (SCD), Vaso-occlusion is a complex process involving increased adhesion molecule expression, Intravascular hemolysis and the resultant scavenging of nitric oxide, Apply guideline based care to adults with SCD, Exchange transfusion can be used when a simple transfusion may lead to hyperviscosity, Treatment using Hydroxyurea or L-glutamine, Neurocognitive dysfunction as a complication of SCD
Archived at 2025/09/30